Contribution of galaxies to the background hydrogen-ionizing flux - Devriendt, J; Sethi, S; Guiderdoni, B; Nath, B (Oxford University Press, 1998)
We estimate the evolution of the contribution of galaxies to the cosmic background flux at 912 Å by means of a semi-analytic model of galaxy formation and evolution. Such modelling has been quite successful in reproducing the optical properties of galaxies. We assume that high-redshift damped Lyman α systems are the progenitors of present-day galaxies, and we design a series of models that are consistent with the evolution of cosmic comoving emissivities in the available near-infrared, optical, ultraviolet and far-infrared bands along with the evolution of the neutral hydrogen content and average metallicity of damped Lyman α systems. We use these models to compute the galactic contribution to the Lyman-limit emissivity and background flux for 0 ≃ z ≤ 4. We take into account the absorption of Lyman-limit photons by H I< and dust in the interstellar medium of the galaxies. We find that the background Lyman-limit flux due to galaxies might dominate (or be comparable to) the contribution from quasars at almost all redshifts if the absorption by H I in the interstellar medium is neglected. Such H I absorption would result in a severe diminishing of this flux — by almost three orders of magnitude at high redshifts and by one to two orders at z ≃ 0. Though the resulting galaxy flux is completely negligible at high redshifts, it is comparable to the quasar flux at z ≃ 0.